1931
DOI: 10.1152/ajplegacy.1931.97.2.286
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of the Diuretic Action of Secretin Preparations

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1945
1945
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Early studies with crude secretin suggested that it might have a diuretic action (8,9). The present study shows that glucagon and secretin given in pharmacological doses have a diuretic action in the dog.…”
supporting
confidence: 60%
“…Early studies with crude secretin suggested that it might have a diuretic action (8,9). The present study shows that glucagon and secretin given in pharmacological doses have a diuretic action in the dog.…”
supporting
confidence: 60%
“…They therefore concluded that the diuretic effect of secretin was most likely contributed by the impairment of sodium reabsorption in renal tubule caused by an increase in renal plasma flow as a result of dilation of the renal vascular bed. A consistent diuretic effect of secretin was also demonstrated in dogs (Dragstedt & Owen 1931). Different secretin preparations were extracted from the mucosa of the first six feet of the hog's intestine and all these preparations were found to produce significant diuresis after i.v.…”
Section: The Pharmacological Actions Of Secretin In the Kidneymentioning
confidence: 58%
“…The renal function in early studies 127 with impure preparations of secretin suggested a diuretic action of secretin opposing the antidiuretic effects of Vp and SS 128 . Subsequent studies by Baron et al , 129 Barbezat et al , 130 Viteri et al , 131 and Waldum et al 132 consistently indicated the diuretic activity of secretin, while studies by Charlton et al 133 showed an antidiuretic function of this peptide.…”
Section: Introductionmentioning
confidence: 98%